Multiscale computational modeling of thermomechanical fracture in cementitious materials with application to recycled aggregate concrete - Gimenes, Marcela [UNESP] (2025)
A multiscale computational model is proposed to investigate the fracture behavior of cementitious materials, including recycled aggregate concrete. The model evaluates the thermomechanical response of the material by explicitly representing aggregates (natural and recycled), mortar matrix, interfacial transition zones and reinforcements. The central hypothesis is that refining the analysis scale enables the natural reproduction of macroscopic behaviors otherwise difficult to capture. To model the complex compressive failure mechanism, a combination of tensile and a shear-frictional damage models is employed. The Mesh Fragmentation Technique with high aspect ratio interface elements is used in a fully coupled thermomechanical framework. Additionally, a condensed twolayer interface element independently governed by distinct damage models is proposed. The results obtained align with experimental data, highlighting the critical influence of heterogeneous mesostructure on fracture mechanisms at both room and elevated temperatures. The methodology was tested in 2D and 3D for concrete specimens with varying mesoscopic compositions, geometries and material properties, verifying the predictive capability under varied conditions. The model effectively reproduced key features of the material response, including the sensitivity to friction conditions in compression tests, the influence of specimen slenderness, and the impact of recycled aggregate replacement ratio on the resulting stress–strain curves. A parametric sensitivity analysis further highlights the predominance of mode-II parameters in specimens under compression. Additionally, a stochastic thermomechanical analysis was conducted, incorporating random fields of material properties to evaluate the variability of the structural response. This approach effectively demonstrated the role of material heterogeneity in the degradation of mechanical properties at elevated temperatures.